Geographical Distribution of the Giardia Lamblia in Male Patients of Mazandaran Province from 1992 to 2013 - Ghanbarpour, Fatemeh; Sharif, Mahdi; Ghoulami, Shirzad; Hoseiny, Mahboobeh; Sharifian, Rayka; Dalaeli, Ali (Archives of Men's Health, 2020)
Introduction: Intestinal parasites of humans are important health problems of most communities, especially those situated in tropical and subtropical areas. This review study was done on the population of Mazandaran Province, northern Iran, during 1991-2013, to gain a better understanding of the distribution of intestinal protozoan parasite, Giardia Lambelia, in this province by providing a geographic map. Material and Method: This review was performed by collecting the data through international search engines such PubMed, ScienceDirect, Google Scholar, SID, Magiran and postdoctoral theses. Data were classified and analysed by SPSS software. Then Data applied to the map by ArcGIS software. Results: According to our study, the maximum level of infection with Giardia Lamblia between male patients was seen in Tonekabon in 1982 and the Prevalence of this intestinal parasite in the western regions of the province was more than other regions. The prevalence of Giardia decreased After 23 years. Discussion: The prevalence of intestinal protozoan parasite, Giardia Lambelia, among people of Mazandaran Province is still very high which necessitates performing special control measures.